LANGUAGE OF LOVE: KAFKA’S AFFECTIVE MEANING IN BRIEFE AN MILENA - Triny, Kafka Aisyah; Wulandari, Julia (International Review of Humanities Studies, 2025)
Franz Kafka is known for his twisted literature filled with dark atmosphere and word choices, however when it comes to writing letters to his muse, Milena, he uses words unknown to him. He expresses his barest soul to her using word choices that indicate someone who is amazed. For a person like Kafka, love is not all about complementing word choices and emotions, seen by his internal battles with himself and uncertainty regarding the topic of love. This research will use Geoffrey Leech’s semantic framework along with Monica Schwarz and Jeannette Chur’s Wortfeld theory. The study aims to examine Kafka’s use of intricate words to convey his love. The findings reveal that Kafka’s chosen word choices reflect how he views love and his unlucky experience of love. His word choices can be categorized into contrasting emotions and how his understanding of love is both a dream and a nightmare.